Efektivitas Penyuluhan Stunting Pada Anak di Desa Meugit Kaye Panyang Kecamatan Bandar Dua Kabupaten Pidie Jaya - Ambia Nurdin; Mutadhahadi Mutadhahadi; Rizka Auva Rafiqi; Amiruddin Amiruddin; Zakiyuddin Zakiyuddin; Ricky Dear Fitria; Fauzi Aldina; Hendra Cipta; Muhammad Haikal (Lembaga Pengembangan Kinerja Dosen, 2024)
According to the WHO report quoted from Riskesdas in 2018 the target of stunting in Indonesia was 20% but in 2013 the stunting rate was 37.2% but in 2018 there was a decrease to 30.8%. This study used a pre-experimental design with the type of one group pretest-posttest design. In the study the independent variable was the provision of education about stunting, while the dependent variable was the knowledge of the women of Meugit kaye panyang village, kec. City of two, district. Pidie triumph. The questionnaire in this study was used to examine the effect of counseling about stunting on increasing the knowledge of meugit kaye panyang village women. The number of samples taken was 17 respondents. It is known that knowledge before being given counseling is categorized as high by 5 respondents or 29%. It can be seen that knowledge after being given counseling is categorized as high by 17 respondents or 100%. It is known that there was an increase in the average knowledge of the respondents after being given counseling where the measurement results showed that all respondents obtained scores in the high category, these results showed positive results from the counseling process carried out.